Interurban Corporate Headquarters Relocation in Canada - Semple, R.; Green, Milford (Cahiers de géographie du Québec, 1983)
This study examines the interurban migration of corporate headquarters in Canada for the period 1970-1982 by investigating the premise that changing socio-economic and political conditions are contributing to the relocation of corporate headquarters. The paper demonstrates that in Canada corporate relocations are tending to create a spatially more concentrated location pattern.